PENGARUH MOTIVASI MEMASUKI DUNIA KERJA DAN PRESTASI BELAJAR TERHADAP KESIAPAN KERJA MAHASISWA JURUSAN PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Nia Junaidi; Armida Silvia; Dessi Susanti (Universitas Negeri Padang, 2018)
This study aimed to examine the effect of motivation to enter the workforce and workplace readiness achievement of learning on students majoring in economics education field state university economic faculties. This research is causative. The population in this study were all students majoring in economics education UNP force in 2014 by using primary data and secondary data. The analytical method used is multiple regression analysis using SPSS version 17. The results of this study indicate that 1) the motivation to enter the workforce a significant effect on job readiness of students majoring in economics education field state university economic faculties 2) The learning achievement no significant effect on job readiness economic education student state university economic faculties desert 3) Motivation to enter the world of work and learning achievements jointly significant effect on job readiness of students majoring in economics education field state university economic faculties.Keywords: Motivation entering the world of work, academic achievement and job readiness